NEW RECORD OF LIGULA INTESTINALIS (LINNAEUS, 1758) (CESTODA: PSEUDOPHYLLIDEA) INFECTION IN HYPSELOBARBUS THOMASSI FROM THE WESTERN GHATS OF KERALA - VIJAYALAKSHMI, P. V.; JOSE, WILLIAMS J. JEAN; KARIM, L. RAZEENA; VISHNU NAIR, M. S. (Journal of the Inland Fisheries Society of India, 2021)
The tapeworm Ligula intestinalis (L.) is the most common species of the genus Ligula and is widely distributed throughout the northern hemisphere (Dubinina, 1980). It has recently been also reported from southwestern Australia (Morgan, 2003; Chapman et al., 2006). This pseudophyllidean cestode presents a complex life cycle with a cyclopoid or diaptomid copepod as first intermediate host and planktivorous fish as second intermediate host. Fish-eating birds serve as the final host in which L. intestinalis quickly reaches sexual maturity and releases eggs. The worms acquire maturity in 3-5 days in the bird host and infected piscivorous birds are scarcely observed in natural conditions (Loot et al., 2001). The most conspicuous stage within the life cycle is the plerocercoid. Although it develops in the abdominal cavity of the second intermediate host and has a considerable effect on fish health, fecundity and behaviour. As a result it can cause heavy losses in freshwater pisciculture (Arme and Owen, 1968; Carter et al., 2005). Particularly reported from cyprinid fish, L. intestinalis has been shown to utilize a broad range of hosts, including other fish families such as Catostomidae, Salmonidae or Galaxiidae (Dubinina, 1980; Chapman et al., 2006).